Asia–Pacific consensus recommendations for endoscopic and interventional management of hilar cholangiocarcinoma. Issue 4 (25th March 2013) - Rerknimitr, Rungsun; Angsuwatcharakon, Phonthep; Ratanachu‐ek, Thawee; Khor, Christopher J L; Ponnudurai, Ryan; Moon, Jong Ho; Seo, Dong Wan; Pantongrag‐Brown, Linda; Sangchan, Apichat; Pisespongsa, Pises; Akaraviputh, Thawatchai; Reddy, Nageshwar D; et al.
Abstract Hilar cholangiocarcinoma (HCCA) is one of the most common types of hepatobiliary cancers reported in the world including Asia–Pacific region. Early HCCA may be completely asymptomatic. When significant hilar obstruction develops, the patient presents with jaundice, pale stools, dark urine, pruritus, abdominal pain, and sometimes fever. Because no single test can establish the definite diagnosis then, a combination of many investigations such as tumor markers, tissue acquisition, computed tomography scan, magnetic resonance imaging/magnetic resonance cholangiopancreatography, endoscopic ultrasonography/intraductal ultrasonography, and advanced cholangioscopy is required. Surgery is the only curative treatment. Unfortunately, the majority of HCCA has a poor prognosis due to their advanced stage on presentation. Although there is no survival advantage, inoperable HCCA managed by palliative drainage may benefit from symptomatic improvement. Currently, there are three techniques of biliary drainage which include endoscopic, percutaneous, and surgical approaches. For nonsurgical approaches, stent is the most preferred device and there are two types of stents i.e. plastic and metal. Type of stent and number of stent for HCCA biliary drainage are subjected to debate because the decision is made under many grounds i.e. volume of liver drainage, life expectancy, expertise of the facility, etc. Recently, radio‐frequency ablation and photodynamic therapy are promising techniques that may extend drainage patency. Through a review in the literature and regional data, the Asia–Pacific Working Group for hepatobiliary cancers has developed statements to assist clinicians in diagnosing and managing of HCCA. After voting anonymously using modified Delphi method, all final statements were determined for the level of evidence quality and strength of recommendation.